Ethical issues in psychosurgery - Golebiowska, Maria; Golebiowska, Beata; Liu, Wei Chen; Zienkiewicz, Ewa (Journal of Education, Health and Sport, 2017)
Psychosurgery, a discipline that emerged from psychiatry and neurosurgery, is a unique form of treatment, even nowadays counted as a last resort for psychiatric patients. With the rapid growth of alternative psychiatric treatment options, the ethical issues related to those procedures. The purpose of this study is to present ethical dilemmas related to psychosurgery. Among the 261 articles related to the ethics of psychosurgery for analysis 14 significant articles were selected. Since the beginning of its existence, psychosurgery encountered several ethical isssues. Starting from its development in 20th century, when the favourable results encouraged more extensive research in this field until its first dawn, when the researchers of the New World introduced it even to non-medical professionals. Nowadays, since medicine starts to realize its limitations in terms of pharmacotherapy and psychotherapy, the psychosurgery comes back from the unpleasant history pages. Modern ethical issues include the most importantly basic ethical principles, which are crucial especially for psychiatric patients. The next important aspect is the modification of beahviour in aggressive behaviour, sociopathic patients and the threat that it will be used as a tool for behaviour modifications rather than treatment method. The positive aspect of nowadays psychosurgery is its impact on increasing the free will in patients with OCD and addiction. Psychosurgery is one of the interesting and beneficial therapeutic options for patients struggling with treatment-resistant psychiatric disorders. The most important is to take into account the basic ethical principles and the greatest willingness to cure the patient into account while performing the psychosurgical operations.